1996
DOI: 10.1172/jci118875
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic iron deprivation prevents spontaneous development of fulminant hepatitis and liver cancer in Long-Evans Cinnamon rats.

Abstract: Several clinical studies have suggested that excess hepatic iron accumulation is a progressive factor in some liver diseases including chronic viral hepatitis and hemochromatosis. However, it is not known whether iron-induced hepatotoxicity may be directly involved in hepatitis, cirrhosis, and liver cancer. The Long-Evans Cinnamon (LEC) rat, which accumulates excess copper in the liver as in patients with Wilson's disease, is of a mutant strain displaying spontaneous hemolysis, hepatitis, and liver cancer. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
75
1
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(79 citation statements)
references
References 32 publications
2
75
1
1
Order By: Relevance
“…31) Copper and/or hemolysis-induced iron accumulation are considered to play roles in hepatocarcinogenesis in LEC rats, because copper-induced hemolysis occurs in the period of necrotizing hepatitis, and iron-deficient diet prevents the development of liver tumors. 32,33) In the present study, despite the diffuse periportal hemosiderosis of hepatocytes (data not shown) and the increased hepatic iron concentration the incidence of hepatocellular tumors in D-penicillamine-treated LEC rats was lower than that in controls, although we did not measure metal concentrations during the period of jaundice.…”
Section: Discussioncontrasting
confidence: 57%
“…31) Copper and/or hemolysis-induced iron accumulation are considered to play roles in hepatocarcinogenesis in LEC rats, because copper-induced hemolysis occurs in the period of necrotizing hepatitis, and iron-deficient diet prevents the development of liver tumors. 32,33) In the present study, despite the diffuse periportal hemosiderosis of hepatocytes (data not shown) and the increased hepatic iron concentration the incidence of hepatocellular tumors in D-penicillamine-treated LEC rats was lower than that in controls, although we did not measure metal concentrations during the period of jaundice.…”
Section: Discussioncontrasting
confidence: 57%
“…However, excess iron is a risk for various cancers (12,14,15). For example, hepatocytes infected with hepatitis virus B or C accumulate iron through iron dysregulation by low hepcidin, and are frequently transformed to hepatocellular carcinoma (16). Indeed, iron reduction can lower the risk for hepatic cancer (17) and probably in other cancers (18).…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22] Iron-deficient diet also inhibits the development of liver tumors. 23) These data suggest that tumor development in LEC rats is a later event caused by chronic copper and/or iron toxicity.…”
Section: Discussionmentioning
confidence: 87%